1996
DOI: 10.1023/a:1016064320334
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Although more of the smaller (2 microns) particles are taken up, particularly by epithelial tissues, the 6 microns size appears more efficient in terms of volume translocated to lymph nodes. This could have implications in the therapeutic use of particles for drug and vaccine delivery and for radiation safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…LSs are approximately 25 μm in size. Previous studies investigating oral transport of particles have determined that particles approximately 2 μm or less are appropriately-sized for uptake via M-cells of the Peyer's patches [44]. However, the same study also reported uptake of 20 μm diameter particles, although with reduced frequency.…”
Section: Resultsmentioning
confidence: 98%
“…LSs are approximately 25 μm in size. Previous studies investigating oral transport of particles have determined that particles approximately 2 μm or less are appropriately-sized for uptake via M-cells of the Peyer's patches [44]. However, the same study also reported uptake of 20 μm diameter particles, although with reduced frequency.…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, whole-body inhalation exposure to ultrafine carbon particles have suggested some deposition in the liver, which has been speculated to originate from gastro intestinal exposure and uptake from the gut (Oberdörster et al 2002). In addition, the uptake of C 60 fullerenes and polystyrene latex microspheres from the gastrointestinal tract into blood circulation has been estimated in the range of 1% of the applied dose (Carr et al 1996; Yamago et al 1995). However, it is interesting to note that in drug delivery research, there is acceptance that particulate matter can be absorbed from the gastrointestinal tract, and this feature of nanomaterials is being used as an approach of altering the pharmacokinetic behavior of drugs (Florence 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Particles (1–2 µm) have been shown to be effective in inducing an immune response because the particles can be selectively taken up by the M cells and can be actively transported across the epithelium [93]. They can also selectively target either M cells or other intestinal cells such as enterocytes by use of targeting moieties or by incorporating mucoadhesive polymers [55].…”
Section: Mucosal Vaccine Delivery Systemsmentioning
confidence: 99%